The Use Of Self-Talk Strategy To Improve Students’ Speaking Skill At The First Grade, Semester 1. Academic Year of 2021/2022 of SMK XYZ - Lulu Humairoh (JOLADU: Journal of Language Education, 2022)
The method of the research that is used by the writer is a qualitative approach in classroom action research method by researcher participant. The classroom action research is a method of finding out what works best in your own classroom so that you can improve students’ learning. The subject of the research is all of the students at SMK XYZ. This research uses one class. The researcher chooses the first class and concept of 20 students. The researcher teached English by Self-talk strategy to improve their speaking skill and the online learning research. In every cycle the researcher made lesson plans, actions, observations and reflecting to know how far the learning process can improve students’ speaking skill. From the researcher's result. The learning target of students in cycle one is 51%, then in cycle two the learning target increased to 69%. In the last cycle the learning target increased again, becoming 76%. Based on the result above, that self-talk strategy can improve the students’ speaking skill. It’s known from the learning target in each cycle that continuously increases. So, the researcher concludes that self-talk strategy can improve the students’ speaking in the teaching learning process.